Drug-Induced Acute-on-Chronic Liver Failure in Asian Patients. (June 2019) - Devarbhavi, Harshad; Choudhury, Ashok Kumar; Sharma, Manoj Kumar; Maiwall, Rakhi; Al Mahtab, Mamun; Rahman, Salimur; Chawla, Yogesh K.; Dhiman, Radha K.; Duseja, Ajay; Taneja, Sunil; Ning, Qin; Jia, Ji Dong; et al.
Abstract : OBJECTIVES: Acute insults from viruses, infections, or alcohol are established causes of decompensation leading to acute-on-chronic liver failure (ACLF). Information regarding drugs as triggers of ACLF is lacking. We examined data regarding drugs producing ACLF and analyzed clinical features, laboratory characteristics, outcome, and predictors of mortality in patients with drug-induced ACLF. METHODS: We identified drugs as precipitants of ACLF among prospective cohort of patients with ACLF from the Asian Pacific Association of Study of Liver (APASL) ACLF Research Consortium (AARC) database. Drugs were considered precipitants after exclusion of known causes together with a temporal association between exposure and decompensation. Outcome was defined as death from decompensation. RESULTS: Of the 3, 132 patients with ACLF, drugs were implicated as a cause in 329 (10.5%, mean age 47 years, 65% men) and other nondrug causes in 2, 803 (89.5%) (group B). Complementary and alternative medications (71.7%) were the commonest insult, followed by combination antituberculosis therapy drugs (27.3%). Alcoholic liver disease (28.6%), cryptogenic liver disease (25.5%), and non-alcoholic steatohepatitis (NASH) (16.7%) were common causes of underlying liver diseases. Patients with drug-induced ACLF had jaundice (100%), ascites (88%), encephalopathy (46.5%), high Model for End-Stage Liver Disease (MELD) (30.2), and Child-Turcotte-Pugh score (12.1). The overall 90-day mortality was higher in drug-induced (46.5%) than in non–drug-induced ACLF (38.8%) ( P = 0.007). The Cox regression model identified arterial lactate ( P < 0.001) and total bilirubin ( P = 0.008) as predictors of mortality. DISCUSSION: Drugs are important identifiable causes of ACLF in Asia-Pacific countries, predominantly from complementary and alternative medications, followed by antituberculosis drugs. Encephalopathy, bilirubin, blood urea, lactate, and international normalized ratio (INR) predict mortality in drug-induced ACLF.